Program for Improving Facilities and Tourist Attractions at the Culture and Tourism Office of North Sumatra Province - Hutauruk, Indah Swanti (Cattleya Darmaya Fortuna, 2024)
Tourist attractions are locations specifically visited by travelers seeking leisure, entertainment, or cultural experiences. In this research, the availability of facilities and the attractiveness of tourist objects are identified as critical factors in increasing tourist visits to North Sumatra. Currently, tourism development in the region is managed under the authority of the Department of Culture and Tourism of North Sumatra, which is responsible for planning, regulating, and guiding tourism development comprehensively. This study aims to address the following research questions: (1) What are the development programs for tourist facilities and attractions in North Sumatra? (2) What initiatives have been undertaken in terms of object development and tourism businesses? (3) What efforts have been made to improve tourism facilities and attractions in North Sumatra? The research adopts a descriptive qualitative method, and data were collected through field research at the North Sumatra Provincial Department of Culture and Tourism. The findings of this research indicate that: (1) The current state of facilities at tourist sites in North Sumatra is generally good, and existing development programs have been implemented effectively. Facilities are sufficiently comfortable and contribute positively to tourist experiences. (2) The 2020 tourism facility development programs have been fully completed, particularly in terms of object development and business support. (3) Continuous improvements in facilities and attractions have significantly influenced tourist interest and satisfaction. Cleanliness, comfort, and completeness of infrastructure remain top priorities for enhancing tourist appeal. The collaboration between the tourism management and the North Sumatra regional government continues to support efforts in providing high-quality facilities across tourism destinations. The study suggests that the development of tourism destinations is highly dependent on the quality and availability of supporting infrastructure. Therefore, it is recommended that both local government and tourism stakeholders continuously upgrade and maintain the quality of these facilities to attract more visitors and boost regional economic growth.